Implementing scripted conversations by means of smart assistants. (20th December 2022) - Pacheco‐Lorenzo, Moisés; Fernández‐Iglesias, Manuel J.; Valladares‐Rodriguez, Sonia; Anido‐Rifón, Luis E.
Abstract: Smart assistants are among the most popular technological devices at home. With a built‐in voice‐based user interface, they provide access to a broad portfolio of online services and information, and constitute the central element of state‐of‐the‐art home automation systems. This work discusses the challenges addressed and the solutions adopted for the design and implementation of scripted conversations by means of off‐the‐shelf smart assistants. Scripted conversations play a fundamental role in many application fields, such as call center facilities, retail customer services, rapid prototyping, role‐based training or the management of neuropsychiatric disorders. To illustrate this proposal, an actual implementation of the phone version of the Montreal cognitive assessment test as an Amazon's Alexa skill is described as a proof‐of‐concept.